Virtual Electrode Design for Lithium‐Ion Battery Cathodes. Issue 6 (14th January 2021) - Joos, Jochen; Buchele, Alexander; Schmidt, Adrian; Weber, André; Ivers-Tiffée, Ellen
Abstract : Microstructural characteristics of lithium‐ion battery cathodes determine their performance. Thus, modern simulation tools are increasingly important for the custom design of multiphase cathodes. This work presents a new method for generating virtual, yet realistic cathode microstructures. A precondition is a 3D template of a commercial cathode, reconstructed via focused ion beam/scanning electron microscopy (FIB/SEM) tomography and appropriate algorithms. The characteristically shaped micrometer‐sized active material (AM) particles and agglomerates of nano‐sized carbon‐binder (CB) particles are individually extracted from the voxel‐based templates. Thereby, a library of roughly 1100 AM particles and 20 CB agglomerates is created. Next, a virtual cathode microstructure is predefined, and representative sets of AM particles and CB agglomerates are built. The following re‐assembly of AM particles within a predefined volume box works using dropping and rolling algorithms. Thereby, one can generate cathodes with specified characteristics, such as the volume fraction of AM, CB and pore space, particle‐size distributions, and gradients thereof. Naturally, such a virtual twin is a promising starting point for physics‐based electrochemical performance models. The workflow from the commercial cathode microstructure through to a full virtual twin will be explained and assessed for a blend cathode made of the two AMs, LiNiCoAlO2 (NCA) and LiCoO2 (LCO). Abstract : This work provides a new approach for generating virtual, yet realistic cathode microstructures with predefined characteristics. The workflow from the commercial cathode microstructure through to a full virtual twin will be explained and assessed for a blend cathode made of LiNiCoAlO2 (green) and LiCoO2 (yellow).